A novel decision support model for satisfactory restaurants utilizing social information: A case study of TripAdvisor.com - Zhang, Hong-yu; Ji, Pu; Wang, Jian-qiang; Chen, Xiao-hong (Tourism management (1982), 2017)
Decision support models for satisfactory restaurants have attracted numerous researchers' attention. Many extant models do not consider the active, neutral and passive information in online reviews all at once. Moreover, they ignore the effect of interdependence among criteria on tourists' decision-making. To cover these defects, this study proposes a restaurant decision support model using social information for tourists on TripAdvisor.com. The model introduces fuzzy sets to denote online reviews and utilizes Bonferroni mean to consider interdependence among criteria. Furthermore, it uses a novel similarity measurement which can handle sparse data in fuzzy environments. To validate the model, we conduct a case study of TripAdvisor.com which compares the proposed model with four other models. The performance of each model is evaluated by the metric called the mean absolute error. The study shows that the proposed model can effectively support tourists' decision-making and it performs better than the other four models. •A novel restaurant decision support model for TripAdvisor.com is established.•Fuzzy sets are introduced to describe tourists' review information.•A similarity method is developed to deal with sparse data.•Bonferroni mean are introduced to consider interdependence among criteria.•The model is tested through a case study of TripAdvisor.com.